Dynamics of Nutrient Concentrations, Endogenous Hormones, Photosynthetic Capacity, and Phenological Changes in Black Orchid (Coelogyne pandurata Lindl.) from the Vegetative to Generative Phase - Heriansyah, Pebra; Aziz, Sandra Arifin; Sukma, Dewi; Nurcholis, Waras (Journal of Tropical Crop Science, 2025)
The black orchid (Coelogyne pandurata Lindl.) is one of the native Indonesian orchids from Borneo island. This study analyzed the dynamics of pigments, photosynthetic capacity, endogenous hormones, nutrient concentrations, and phenology across the vegetative to generative stages of the black orchid. The plant materials are one-year-old plants after splitting from the mother plants. Endogenous hormones, nutrient and pigment concentrations, and leaf photosynthetic capacity were measured during vegetative and generative phases. Chlorophyll, anthocyanins, and carotenoids were analyzed using UV-VIS spectrophotometry, Nitrogen (N) was analyzed by the Kjeldahl method, phosphorus (P) and potassium (K) by the Bray 1 method and Flame Photometry, and organic carbon by the Walkley- Black method with titration. The hormone levels were analyzed using HPLC, and photosynthetic capacity was determined using a Li-Cor 6800 system. Phenological changes in leaves, bulbs, and flowers were recorded. Results showed total chlorophyll increased from 1.96 to 2.36 mg/g from the vegetative to the generative stage while carotene slightly declined. Leaf nitrogen rose from 1.54% to 1.70%, bulb nitrogen decreased from 0.67% to 0.45%, whereas the C/N ratio increased from 65.24 to 85.36 from the vegetative to the generative phase. Flower nitrogen was 1.50%, and phosphorus was 0.17%. IAA in leaves decreased from 25.12 to 21.37 ng.g⁻¹ dry weight post-flowering, while gibberellin in bulbs increased from 12.28 to 12.96 ng.g⁻¹ dry weight. Zeatin in bulbs declined from 10.52 to 8.81 ng g⁻¹ dry weight. Photosynthesis peaked at 2.73 μmol. m⁻².s⁻¹ in early generative stages and then declined. Photosynthetic photon flux density and stomatal conductance decreased, reducing water and CO₂ exchange efficiency, while net assimilation and transpiration rates showed no significant changes. These physiological adjustments, including increased chlorophyll levels, changes in nitrogen allocation, and fluctuations in hormone concentrations, reflect the plant’s adaptive strategies to meet higher energy demands during reproductive growth, ensuring efficient resource distribution for flowering.